THE ROLES OF THE SUPREME COURT OF THE REPUBLIC OF INDONESIA IN ENFORCEMENT OF INTERNATIONAL ARBITRAL AWARDS IN INDONESIA - Hikmah, Mutiara (Indonesia Law Review, 2013)
Indonesia has been being a member of the 1958 New York Convention since 1981, namely upon issuance of the Presidential Decree No. 34 of 1981. Prior to taking into force of the Regulation of the Supreme Court of the Republic of Indonesia No. 1 of 1990 on Procedures for Enforcement of Foreign Arbitral awards, there were still constraints for the foreign business players in term of enforcement of arbitral awards in Indonesia. The Supreme Court as the highest judicial institution in Indonesia holds that international arbitral awards can not be enforced in Indonesia. After the Indonesian Supreme Court has issued such a regulation, enforcement of international arbitral awards in Indonesia began to be enforceable, because the procedural law that governs the procedures for execution of arbitral awards has been clear. In order to regulate better the international arbitral award problems in the hierarchy of legislation, on October 12, 1999, the Law on Arbitration and Alternative Dispute Resolution was promulgated. In that Law, there is a special part discussing the International Arbitration. This study examines the development of international arbitral award enforcement in Indonesia before Indonesia becoming member of the 1958 New York Convention, until nowadays, by analyzing the international arbitral awards that were decided by the Supreme Court of the Republic of Indonesia after the coming into effect of the Arbitration Law